Muslim at the Margin: understanding their changing occupations in Hyderabad - K. M. Ziyauddin, (IJRDO - Journal of Social Science and Humanities Research, 2018)
The historical background of Hyderabad city shows the existence of glorious society in past. The hierarchies among Muslims were not based on caste identification but it happens to be on the bases of occupation. Of the various social groups of Muslims in existence in Andhra Pradesh, only Dudekula or Pinjari or Nurbash has been known, identified and referred to since a long time. Two recent accounts of social groups of Muslims of Andhra Pradesh mentioned one in ‘People of India’ series volume of Anthropological Survey of India on Andhra Pradesh. Saheb, mentions that “the Indian Muslims also have caste-like groups” but he distinguishes them from Hindu caste in that Muslim caste lack an ideological frame comparable to the traditional Hindu varna model. The paper will draw a brief profile of the Muslim scavengers and those engaged in unclean occupation in the district of Hyderabad. This will enable to explore the various aspects of societal intercourse and interaction of this community with the larger society and also social exclusion how the field creates challenges to the fieldworker.